Menstrual blood-derived mesenchymal stromal cell secretome modulates macrophage polarization in a preconditioning-dependent manner - de Pedro, María Ángeles; Pulido, María; Marchena, Ana María; Álvarez, Verónica; González-Nuño, Francisco Manuel; Szymański, Witold; Pörschke, Johanna; Reinartz, Silke; Graumann, Johannes; Pogge von Strandmann, Elke; Sánchez-Margallo, Francisco Miguel; Gómez-Serrano, María; et al. (Frontiers in Cell and Developmental Biology, 2026)
BackgroundThe effects of menstrual blood-derived mesenchymal stromal cell secretome (S-MenSC) on macrophage polarization remain unclear. This study studied the impact of secretomes from basal MenSCs (S-bMenSCs) and those preconditioned with IFNγ and TNFα (S-pMenSCs) on human monocytes and macrophages in vitro.MethodsS-MenSCs were used to assess their effects on three stages of monocyte-derived cell maturation: i. monocyte differentiation; ii. polarization of monocyte-derived macrophages (MDMs) toward M1-like or M2-like phenotypes; and iii. reprogramming of pre-polarized M1 or M2 macrophages. Surface markers were analyzed by flow cytometry and cytokine gene expression by RT-qPCR. In addition, a proteomic profiling was performed to identify proteins involved in the observed effects.ResultsOur results confirmed the capacity of S-MenSCs of modulating innate immune response and in particular macrophage polarization. More concretely, the in vitro experiments showed that: i. both secretomes partly promoted monocyte differentiation into an M1-like phenotype; ii. during macrophage polarization, S-bMenSCs partially limited the shift to an M1 phenotype, whereas treatment with S-pMenSCs boosted it; and, iii. in the pre-polarized macrophages, S-bMenSCs reinforced M1 traits, whereas S-pMenSCs promote partial phenotype switching. Finally, proteomic analysis revealed significant differences in the composition of both secretomes, comprising key proteins associated with macrophage polarization.ConclusionThese findings extend the knowledge on the immunomodulatory capacity of the S-MenSC, supporting that MenSCs, particularly when preconditioned, may play a significant role in regulating macrophage polarization, and, thus, modulating the inflammatory response.